INDIRECT SPEAKING IN ENGLISH AND JAVA (A CONTRASTIVE ANALYSIS) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2022)
This study discusses about Indirect speech in English and Javanese Language. The question in this research is what are the kind of indirect speech in English and Javanese, and also what are the similarities and differences in indirect sentences in the two languages. This study aims to find, explain categories and analyze indirect speech in English and Javanese in a contrasting. During the data collection of this research, the author asked 2 informants who could speak Javanese well and correctly. The gender of the informants who were asked were men and women aged around 20-40 years who had lived in East Java for 20-40 years. In the English data, the author takes several examples of Indirect Speech sentences from a book written. Then the writer collects all the data and identifies several sentences that have referred to an indirect speech in English and Javanese. Then the author describes the variations of Indirect Speech translated into English and Javanese and compared to find a similarity and some differences in Indirect Speech using the concept of Quick. The results in this study indicate that English has indirect speech likewise as Javanese language and has some similarities and a differences. In terms of similarities, English and Javanese have similarities in their types and shaped like an apostrophe, an interrogative sentence, a statement, command, exclamation and the sentence changes according to time and place. In contrast, English can turn into a verb to be and an auxiliary verb, while Javanese does not. Keywords: Indirect Speech, English and Javanese language, a Contrastive Analysis.
Keywords: Indirect; Speaking; English; Speaking English; Sepaking Java